EDUKASI DISMIS INFORMASI UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMP PGRI TENJOLAYA KABUPATEN BOGOR - Rusdiono Mukri; Lina Najwatur Rusydi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of digital technology in Indonesia is experiencing rapid development. The public, including students, can communicate and obtain information through digital technology. There has been an increase in the younger generation's access to the internet in the last four years, the percentage of the young generation, aged 5 - 24 years, who have internet access has increased from 33.98% to 59.3%. A quarter of internet users, around 25.5% are children and teenagers. However, their lack of digital literacy hinders them to be able to sort and select valid and useful information, and avoid hoax information or issues. This community service activity aimed to increase the knowledge and understanding of Tenjolaya PGRI Middle School students in Bogor Regency regarding digital literacy to avoid the negative impacts of the digital era, especially the internet and social media. This socialization and education was carried out at Tenjolaya PGRI Middle School which is located in Kampung Tegalangkap, Gunung Malang Village, Tenjolaya District, on August 31, 2023. This activity used the socialization method regarding information dissemination education to increase students' digital literacy. Based on the results of the implementation of activities, it can be seen that Tenjolaya PGRI Middle School students' knowledge and understanding of digital literacy is still low.